Characteristics of deceased solid organ donors and screening results for hepatitis B, C, and human immunodeficiency viruses — United States, 2010–2017. Issue 3 (25th February 2019) - Abara, Winston E.; Collier, Melissa G.; Moorman, Anne; Bixler, Danae; Jones, Jefferson; Annambhotla, Pallavi; Bowman, James; Levi, Marilyn E.; Brooks, John T.; Basavaraju, Sridhar V.
Abstract : This report summarizes the increasing use of increased‐risk deceased organ donors, noting the association of HCV and HBV with this designation.